A programmbale 8-channel multiphase clock generator with 360 phases for focus ultrasound applications. (February 2019) - Cheng, Hsiang-Chi; Cheng, Shih-Hung; Kao, Shao-Ku
Abstract: An area efficient, programmable multichannel, multiphase clock generator is proposed to improve the phase resolution for focus ultrasound applications. By using the proposed phase-folding method, the cell amount for generating 360 phases are reduced from 360 to 38 cells. The proposed clock generator is able to provide 360 phases in real-time with 1° phase resolution, 1–51.9% 6-bit DPWM for each channel, and which output frequency varies from 0.1 to 1.5 MHz. Due to the proposed multiphase system is a real-time system, many independent multichannel applications such as focus ultrasound could easily adopt the proposed structure. A new phase-error calibration method for PLL is also present in this paper for reducing the static phase-error due to process voltage and temperature variation. It improves the accuracy of the phase difference in the multiphase system. The proposed ASIC was fabricated in a standard 0.18 μm CMOS process. Measured result shows that multiphase clock generator is able to provide 360 selective phases for each channel. The derived DNL is from −0.106 to +0.108 LSB, and the INL is from −0.284 to +0.449 LSB at 1 MHz.